Determination of Adhesive and Cohesive Strength in Metal Coatings Deposited by Hypersonic Metallization - F. I. Panteleenko; M. N. Karpets; M. A. Belotserkovsky; A. V. Sosnovsky (Наука и техника, 2021)
. It is known that at present, methods of thermal spraying are widely used to restore and strengthen various worn-out machine parts. As a rule, metal coatings applied by thermal spraying have lower strength characteristics than solid materials. It is believed that the strength of coatings is proportional to their adhesive and cohesive strength. The value of adhesive and cohesive strength depends on various factors, including the nature of the materials and the technology of coating. An important factor characterizing the possibility of using metal coatings in various industries is the strength of adhesion of coatings to the base metal. The paper presents the determination of the adhesive and cohesive strength of coatings from different materials, applied by the method of hypersonic metallization. The results of testing the strength of metal coatings made of ER316LSi-grade wire, nichrome (Cr20Ni80) and molybdenum wire are given in the paper. Based on the results of metallographic studies, the proportion of the participation of cohesive and adhesive components in the strength of coatings has been determined, and some features of coating destruction have been described. It has been found that the participation of the cohesive and adhesive components of the coating strength differs depending on the material used. The cohesive component prevails in the strength of coatings made of high-alloy wire of the ER316LSi-grade, at which destruction mainly occurs along the coating-base boundary. For nichrome coatings and especially for coatings made of molybdenum, the cohesive component is predominant, in which the destruction of the coating occurs not along the coating-base boundary, but between the coating layers.